2002
DOI: 10.1034/j.1600-0625.2002.110102.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of pruritus in atopic dermatitis: an overview

Abstract: Pruritus is an essential feature of atopic dermatitis (AD) andImmunobiology of the Skin, University of the diagnosis of active AD cannot be made without the history of Münster, Münster, Germany itching. Because of the high impact on life quality, most of the patients measure the severity of eczema by the intensity of pruritus rather than appearance of skin lesions. However, although pruritus is a cardinal symptom of AD, its mechanism and association with the cutaneous nervous system is not completely understoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
181
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(185 citation statements)
references
References 177 publications
(184 reference statements)
2
181
0
2
Order By: Relevance
“…However, we now know that the sensation of itch and nociception cannot be equated with each other. In fact, the once-popular theories that itch is based on a specific pattern of action potentials running through pain pathways or that itch results from the combination of other primary sensory signals have now fallen out of favor (3,10). Likewise the confirmation of the long-denied existence of central itch-specific neuronal pathways in the human and feline systems supports the concept that the sensation of itch and nociception represent distinct sensory systems (9,11).…”
Section: The Sensation Of Itch and Nociception Are Distinct Entitiesmentioning
confidence: 52%
See 1 more Smart Citation
“…However, we now know that the sensation of itch and nociception cannot be equated with each other. In fact, the once-popular theories that itch is based on a specific pattern of action potentials running through pain pathways or that itch results from the combination of other primary sensory signals have now fallen out of favor (3,10). Likewise the confirmation of the long-denied existence of central itch-specific neuronal pathways in the human and feline systems supports the concept that the sensation of itch and nociception represent distinct sensory systems (9,11).…”
Section: The Sensation Of Itch and Nociception Are Distinct Entitiesmentioning
confidence: 52%
“…TRPV1 activation first excites (84), then desensitizes, the sensory afferents - an effect that establishes the basis for the therapeutic application of vanilloids to mitigate pain and itch (3, S16). Vanilloid administration results in a depletion of neuropeptides (such as SP) in the C-fibers, which suspends the interplay between skin sensory neurons and mast cells (Figure 1) (3,6,10). Indeed, topical capsaicin suppresses histamine-induced itch (86) and is increasingly used in the therapy of pruritus in numerous skin diseases (reviewed in refs.…”
Section: Endovanilloids and The Trpv1 Ion Channel Are Promising Targementioning
confidence: 99%
“…These results suggested that opioid receptor is involved in Gsp-induced USRs. Opioids have been reported to play an interesting role in itch induced not only by histamine release from dermal mast cells but also by a direct central and peripheral pruritogenic effect in addition to their major well-known role in pain (Stander and Steinhoff, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Heat may play a harmful role in some AD patients by provoking perspiration, which is one of the most commonly reported aggravants in children with AD [139][140][141][142][143]. Perspiration may have an irritant effect on the skin mediated by the acidic pH of sweat, possibly promoting Th-2 inflammation [88], increased cutaneous blood flow due to vasodilation in hot environments [142], and possibly a neuroanatomic mechanism mediated by C nerve fibers [144]. The worsening of AD symptoms by increased temperature likely explains patient preference toward lighter clothing, thereby allowing for better skin ventilation and facilitating heat dissipation [86].…”
Section: Climatementioning
confidence: 99%